The backscattering ratio of comet 67P/Churyumov–Gerasimenko dust coma as seen by OSIRIS onboard Rosetta. Issue 3 (22nd October 2018) - Bertini, I; La Forgia, F; Fulle, M; Tubiana, C; Güttler, C; Moreno, F; Agarwal, J; Munoz, O; Mottola, S; Ivanovsky, S; Pajola, M; Lucchetti, A; et al.
ABSTRACT: Remote sensing observations of dust particles ejected from comets provide important hints on the intimate nature of the materials composing these primitive objects. The measurement of dust coma backscattering ratio, BSR, defined as the ratio of the reflectance at phase angle 0° and 30°, helps tuning theoretical models aimed at solving the inverse scattering problem deriving information on the nature of the ejected particles. The Rosetta /OSIRIS camera sampled the coma phase function of comet 67P, with four series acquired at low phase angles from 2015 January to 2016 May. We also added previously published data to our analysis to increase the temporal resolution of our findings. We measured a BSR in the range ∼ [1.7–3.6], broader than the range found in literature from ground-based observations of other comets. We found that during the post-perihelion phase, the BSR is systematically larger than the classical cometary dust values only for nucleocentric distances smaller than ∼100 km. We explain this trend in terms of a cloud of chunks orbiting the nucleus at distances <100 km ejected during perihelion and slowly collapsing on the nucleus over a few months because of the coma gas drag. This also implies that the threshold particle size for the dust phase function to become similar to the nucleus phase function is between 2.5 mm and 0.1 m, taking into account previous Rosetta findings.